Analisis Semiotika Lirik Lagu “Angel Baby” Karya Troye Sivan - Irawan, Deddy; Parapat, Dyah Atika; Sazali, Hasan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The song "Angel Baby" is considered to cause debate in the midst of society, especially Indonesian society. Because this song is consider to contain LGBT elements because the singer is Troye Sivan whose is allegedly gay. Therefore, the author makes the song to be analyzed. According to the writing, the song is quite interesting to research (analysis). In short, based on the author's observation or analysis, it is concluded that the song Angel Baby is a song that contains LGBT content. It's base on the content of the song lyrics and plus the singer who is gay.